1991
DOI: 10.5479/si.00810266.69.1
|View full text |Cite
|
Sign up to set email alerts
|

New Enaliarctos* (Pinnipedimorpha) from the Oligocene and Miocene of Oregon and the Role of "Enaliarctids" in Pinniped Phylogeny

Abstract: .-Three new species of the pinnipedimorph Enaliarctos* are described from the marine late Oligocene and early Miocene (Arikareean and Hemingfordian or early Barstovian correlatives) of coastal Oregon. Enaliarctos tedfordl, new species, is based on a partial cranium from the late Oligocene Yaquina Fonnation. A related new species, Enaliarctos emlongi, is founded on a nearly complete cranium, jaws, and associated skeletal elements from the late Oligocene to early Miocene Nye Mudstone. A third new species, Enalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(134 citation statements)
references
References 11 publications
7
125
1
1
Order By: Relevance
“…2D; Berta et al, 1989;Berta, 1991). Enaliarctos was originally known only from partial skulls and teeth (Mitchell and Tedford, 1973) and was initially interpreted as an otarioid pinniped.…”
Section: Pinniped Evolutionary Historymentioning
confidence: 99%
See 1 more Smart Citation
“…2D; Berta et al, 1989;Berta, 1991). Enaliarctos was originally known only from partial skulls and teeth (Mitchell and Tedford, 1973) and was initially interpreted as an otarioid pinniped.…”
Section: Pinniped Evolutionary Historymentioning
confidence: 99%
“…Enaliarctos was originally known only from partial skulls and teeth (Mitchell and Tedford, 1973) and was initially interpreted as an otarioid pinniped. Subsequent phylogenetic analyses (Wyss, 1988;Berta, 1991) demonstrated that Enaliarctos represented the sister taxon to all other pinnipeds.…”
Section: Pinniped Evolutionary Historymentioning
confidence: 99%
“…This scenario changed during the second half of the 1980s (WYSS, 1987;1988a;1988b;, especially due to the reinterpretation of diagnostic characters, studies of the postcranial skeleton (WYSS, 1988b;WYSS, 1989) and discovery of new fossil species (BERTA, 1991;BERTA, 2001;DAVIS et al, 2004;UHEN, 2007), which supported the idea of an arctoid common ancestor for the Pinnipedimorpha. This hypothesis is also supported by studies based on molecular data (FLYNN et al, 2005;HIGDON et al, 2007;DASMAHPATRA et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…Comparative analysis was based on morphological characters following Berta and Deméré (1986), Berta (1991) and Berta and Wyss (1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation